PENGARUH HARGA TERHADAP USAHA MENINGKATKAN VOLUME PENJUALAN MOBIL XENIA PADA PT. ASTRA DAIHATSU Tbk CABANG MALALAYANG MANADO - Benaino, Christian Almendo; Tampi, Johny R. E.; Tumbel, Tinneke M. (Sam Ratulangi University, 2017)
The existence of competition between automotive products between companies impact on the determination of competitive prices and affordable by consumers to encourage increased sales volume. Thus, this study aims